Dynamics of Tax Compliance of Taxpayers Utilizing Covid-19 Tax Incentives in Bekasi - Rahadian Lungun; Prianto Budi Saptono (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
The tax incentives given during the Covid-19 pandemic aim to improve the investment climate and support the business world in the hope that the taxpayers are resilient and can maintain their businesses. However, after two years of utilizing tax incentives, it is hoped that there should be an improvement in the level of tax compliance. This study aims to discover the dynamics of the Tax Compliance of taxpayers before and after two years of the pandemic begins. This study uses a quantitative approach with Correspondence Analysis (CA) which can be used to analyze the multivariate categorical data. This study data uses a population of cross-sectoral medium-sized taxpayers who are utilizing Covid-19 tax incentives from April 2020 to December 2021 in Bekasi. The dimension of tax obligation measures this study's tax compliance level outcome. The results showed that, as a whole, there is a fluctuation in the average level of tax compliance from 2019 to 2021. However, in 2021 there is a tendency for some sectors to experience a decline in compliance, even though the taxpayers are still utilizing tax incentives.